2010
DOI: 10.1007/s00066-010-2053-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Results of Radiation Therapy for Muscle-Invasive Bladder Cancer

Abstract: Radiotherapy is an effective treatment option in terms of local control and survival even in elderly patients with locally advanced bladder cancer not suitable for cystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 55 publications
(74 reference statements)
3
12
2
1
Order By: Relevance
“…A majority of patients were diagnosed with cT3þ disease clinically, although stage did not correlate with outcome in this small study. A complete response was seen in 65% and after 3 years 52% maintained local control; however, 35% of patients died from bladder cancer [18 ].…”
Section: Muscle Invasive Bladder Cancer: Monotherapy Radiotherapymentioning
confidence: 90%
“…A majority of patients were diagnosed with cT3þ disease clinically, although stage did not correlate with outcome in this small study. A complete response was seen in 65% and after 3 years 52% maintained local control; however, 35% of patients died from bladder cancer [18 ].…”
Section: Muscle Invasive Bladder Cancer: Monotherapy Radiotherapymentioning
confidence: 90%
“…The obtained outcomes are more favorable as compared to conventionally fractionated radiotherapy used in the treatment of invasive bladder cancer. [8][9][10][11] Radical radiotherapy for invasive bladder cancer using hypofractioned regimens of total dose of 52.5-57.5 Gy in 20 daily fractions of 2.6-2.9 Gy is a widespread approach in the United Kingdom. Presented hypofractionated and conventionally fractionated (60-64 Gy in 30-32 daily fractions) radiation schedules are equivalent in terms of toxicity, both acute and late, and treatment results.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] In patients who underwent local conservative treatment, that is TURB followed by radiotherapy, the 5-year overall and disease-specific survival rates were 20-40% and 31-56.8%, respectively. [8][9][10][11] As the cure rates offered by local conservative treatment are significantly inferior to those offered by trimodality bladder-preserving therapies, this approach is used exclusively for patients with MIBC who have to be excluded from chemotherapy for medical reasons. However, the demand for local treatment, involving TURB and radiotherapy, is increasing worldwide especially for the group of elderly patients, with significant co-morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…These results are comparable to Lin et al [22] who reported DFS 54% at 3 years. Langsenhner et al [23] and Maarouf et al [24] reported 40% at 3 years and 39% at 1 year respectively. However those are lower than it was reported by Rincon et al [2] who reported PFS 69% at 3 years, but their protocol was used adjuvant 2-4 cycle of chemotherapy, (taxol, methotrexate, 5 FU, and cisplatin).…”
Section: Figure 2 Bladder Intact Survivalmentioning
confidence: 95%